A Distributed Algorithm for Virtual Backbone Construction with Cellular Structure in WSNs - Yu Xiang; Xiaojuan Liu; Yong Tang; Juncong Xiao; Jun Zhang (International Journal of Distributed Sensor Networks)
The normal node in wireless sensor networks (WSNs) often has no constant energy supply. To make efficient use of limited energy resources significant, a major way to save limited energy resources is constructing a smaller virtual backbone in WSNs. In this paper, we propose a distributed algorithm for virtual backbone construction with cellular structure in WSNs (DBC), which is an improvement of algorithm ABP (Duresi and Paruchuri, 2008) and minimize the distortion of constructed cellular structure by improving the way of calculating strategic points using 1-hop neighbor information. Our simulation results show that algorithm DBC has smaller virtual backbone than algorithm ABP, and the number of backbone nodes is much fewer than that one.